Lacustrine Sediments Bacterial Community Structure Vertical Succession of the Linxia Basin, NE Tibetan Plateau: Significance for Paleoenvironment Reconstruction - Xu, Song; Wang, Jingjing; Zhang, Xiaoxia; Yang, Rong; Zhao, Wei; Huang, Zhiyong; Wang, Yongli (Frontiers in Earth Science, 2022)
Abstract： The Linxia Basin on the northeastern margin of the Tibetan Plateau is a typical temperate arid region. Studying sediments in the marginal basins of the Tibetan Plateau is of great significance for central Asian aridification and global climate change. In particular, due to the close relationship between microorganisms and the environment, studying the microbial communities of sedimentary samples in the Linxia Basin might be used as an effective supplement to climate indicators. However, the profiles of microbial communities in this basin are largely unexplored. In this study, high-throughput 16S rRNA gene sequencing techniques were utilized to explore the bacterial community structure vertical succession in sedimentary samples from different depths of the Linxia Basin. A total of 1,729,658 paired reads distributed within 1,042 phylogenetic amplicon sequence variants (ASVs) from 20 sediment samples and three surrounding soil samples were sequenced. Bacterial community structures from the surrounding soil samples were significantly different from those recovered from the sediment samples. In addition, principal coordinate analysis (PCoA) and PerMANOVA analysis indicated that there was a dramatic change shift event of the community structure at position M311. Shifts in the relative abundances of the most abundant taxa (>1%) and significant variations in bacterial community diversity suggest that there were changes in the community structure responses to different sedimentary layers. Changes in predicted community functions demonstrated that aerobic chemoheterotrophy in the sediment bacterial community has significantly increased over time. Consequently, it is hypothesized that the potential influence of the lithofacies results in a change from an anaerobic system to an aerobic system, possibly accompanied by the significant uplift of the Tibetan Plateau that has previously been associated with enhanced aridity in Central Asia at ~8 Ma. Taken together, these results illustrate the potential for microbial communities to be used as a biological indicator in sediment ecosystems for the reconstruction of paleoenvironments.